Ahead of the Curve: Leveraging Antecedents of Corporate Entrepreneurship to Pull Off Competitive Advantage - Mahmood, Asif; Arslan, Ahmad (Frontiers in Psychology, 2020)
Entrepreneurship is a highly dynamic and important endeavor that spills over to economic, technological, and social canvas of a society in this rapidly changing globalized economy. The purpose of the present quantitative study is to investigate the associations among information and communication technologies, innovation, absorptive capacity, CEO’s temporal leadership, and competitive advantage by considering corporate entrepreneurship as a mediator. These factors have been incorporated because they play a predominant role to vie in a competitive environment for entrepreneurial success and economic growth. We used the response of 460 organizations, acquired on a Likert scale, to examine how antecedents of corporate entrepreneurship contribute toward competitive advantage. Structural equation modeling was employed to analyze the measurement and structural relationships including the mediation effects of corporate entrepreneurship. All the relationships with corporate entrepreneurship were found significant except the direct effect of absorptive capacity on competitive advantage. Hence, the results established corporate entrepreneurship as a mediator to predict competitive advantage partially by information and communication technologies (ICT) use, innovation, and temporal leadership. The findings also reveal that absorptive capacity reaps an entire competitive advantage only through corporate entrepreneurship. Practically, the study would be invaluable for organizations, entrepreneurs, and managers to capture a lot of opportunities in effectively managing scarce resources.